The effectiveness of health education program towards knowledge and attitude on Pap smear among married women in Kuantan, Pahang - Sowtali, Siti Noorkhairina; Daud, Azlina; Yusof, Mazlinda; Abidin, Siti Nurfarahin; Saidi, Roslan (2016)
Introduction: Cervical cancer is one of the world’s common causes of mortality. However many women were lacking in the awareness on the importance of PAP smear screening test. Objectives: The aim of this study is to examine the effectiveness of health education program towards knowledge, attitude and practice on Pap smear among married women in Klinik Kesihatan Balok, Kuantan, Pahang. Methods: This was a prospective cohort quasi-experimental study involving mother from Maternal and Child Clinic, Klinik Kesihatan Balok, Kuantan. All the 60 participants were recruited using systemic sampling methods into experimental and control group. The intervention group had received power point presentation handout and one-to-one teaching approach meanwhile the control group had received information pamphlet before answering the questionnaire. Then, the questionnaires were given to the participants in both group pre and post intervention. Results: The mean score for knowledge domain in experimental group had increased significantly (p=0.001) from 102.80 (±10.867) to 156.27 (±12.671). Meanwhile, for attitude domain, the mean score improved significantly (p=0.001) from 24.77 (±4.673) to 30.37 (±2.297) after health education given. In contrast, the mean score for knowledge domain in control group was not significantly changed (p=0.357) from 110.60 (±13.053) to 113.93 (±16.659). For attitude domain of the control group, the mean score improved significantly (p=0.001) from 26.43 (±4.368) to 29.97 (±2.076) after pamphlets distribution. In terms of practice, only 33.3% respondents in intervention group and 36.7% in control group had performed Pap smear test more than four years ago. Discussion: In experimental group, a rapid increase in knowledge score after health education indicate participants were more knowledgeable. In terms of attitude, most of the respondents answered disagree for negative attitude after health education given. Most of them had intention to continuously performed Pap smear test in the future. This highlighted positive changes after receiving health education. Conclusion: Health educational program were effective in improving knowledge attitude and practice among married women on Pap smear test. The health education program should be a continuous strategies to attract women for undergoing Pap smear test in the future.